The Seven Not-So-Wonders of the World (and other challenges of modern Europeanness) - Derek Rasmussen (Swedish University of Agricultural Sciences, Uppsala. pp.8-16., 2001)
"The Seven Not-So-Wonders of the World' (and other challenges of modern Europeanness). Forests, Trees & People Newsletter. No.44, April 2001. Swedish University of Agricultural Sciences, Uppsala. pp.8-16